Predictors of insomnia among undergraduate students at Hawassa University Sidama, Ethiopia, 2023: a facility-based cross-sectional study - Aschale Wale, Mastewal; Reta, Yared; Addis, Haymanot; Tarekegn, Rahel; Tafese, Mintesnot; Tsega Chekol, Aklile (Frontiers in Psychiatry, 2024)
Background Insomnia is a sleep disorder characterized by difficulty falling asleep, staying asleep, or experiencing poor-quality sleep. People with this problem often have trouble falling asleep at night, wake up frequently during the night, and may wake up too early in the morning and feel tired and not refreshed. This can lead to daytime fatigue, irritability, difficulty concentrating, and impaired functioning in their day-to-day activities. Study is scarce in resource-limited countries such as Ethiopia, particularly concerning the study setting. As a result, this study aimed to assess the prevalence of insomnia and its associated factors among undergraduate students at Hawassa University. Methods An institution-based cross-sectional study design was used. A stratified simple random sampling method was used among 398 study participants. The data were collected using a structured self-administered questionnaire. The outcome variable was assessed by the insomnia severity index (ISI). The data were then gathered by using the Kobo toolbox online and then exported into the Statistical Package for Social Sciences version 27 to analyze the data. Data cleaning and screening were conducted exclusively by the investigators. Descriptive statistics like frequency, percentages, and mean were used. Bivariate and multivariate binary regression were performed. In multivariate binary logistic regression, a p-value of<0.05 was identified as a significantly associated factor with the dependent variable. Results Among 398 students who participated in the study, 81 (20.4%) experienced insomnia. Being female [adjusted odds ratio (AOR) = 2.98; 95% confidence interval (CI) 1.56–5.69], age (AOR = 3.06; 95% CI 1.11–8.45), mild anxiety symptom (AOR = 4.89; 95% CI 1.56–15.37), and mobile device use ≥30 min just before going to sleep (AOR = 7.81; 95% CI 2.34–26.12) were significantly associated with insomnia. Conclusion In this study, the prevalence of insomnia was one-fifth among university students, which is high when compared to another study at the national level. There were significant associations between being female, age, anxiety symptoms, and mobile device use before going to sleep with insomnia. This indicates that there is a need to treat and prevent insomnia in college students, emphasizing the necessity for mental healthcare and ethical technology use.